1993
DOI: 10.1089/aid.1993.9.267
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Disorders and Viral Gene Expression in HIV-1 Transgenic Mice

Abstract: Patients infected with HIV-1 experience several hyperproliferative skin disorders, including seborrheic dermatitis, ichthyosis, and psoriasis. Transgenic mice carrying a subgenomic HIV-1 proviral construct lacking the gag and pol genes were found to develop proliferative epidermal lesions, manifested as diffuse epidermal hyperplasia in homozygous transgenic mice and benign papillomas in heterozygous transgenic mice. Nonpapillomatous skin from both homozygotes and heterozygotes expressed viral RNA, and the vira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 30 publications
2
29
0
Order By: Relevance
“…Nor can we exclude differences in renal metabolism of salt and water, particularly in view of the 10% reduction in weight in the first 24 h. Another possibility is that growth failure in mice homozygous for the transgene relates to abundant expression of viral gene products in skin. In this regard, homozygous neonatal mice uniformly develop a progressive, and potentially debilitating, skin disease characterized clinically by dry, thickened, scaling lesions and histologically by epidermal hyperproliferation and hyperkeratosis (34). Growth-retarded mice transgenic for the infectious HIV-1 provirus were also reported to manifest this phenotype (49).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nor can we exclude differences in renal metabolism of salt and water, particularly in view of the 10% reduction in weight in the first 24 h. Another possibility is that growth failure in mice homozygous for the transgene relates to abundant expression of viral gene products in skin. In this regard, homozygous neonatal mice uniformly develop a progressive, and potentially debilitating, skin disease characterized clinically by dry, thickened, scaling lesions and histologically by epidermal hyperproliferation and hyperkeratosis (34). Growth-retarded mice transgenic for the infectious HIV-1 provirus were also reported to manifest this phenotype (49).…”
Section: Discussionmentioning
confidence: 99%
“…Descriptions of the nephropathy that develops in heterozygous transgenics have been published previously (31,33). Transgenic mice also develop hyperproliferative skin disorders manifested as benign papillomas in heterozygous mice and diffuse epidermal hyperplasia in homozygotes (34). In addition to the skin lesions, homozygous mice develop a syndrome of growth failure and cachexia with lymphoproliferation, preservation of CD4+ and CD8+ T-lymphocyte number, thymic atrophy, and early death (32).…”
Section: Transgenic Micementioning
confidence: 99%
“…Under control of the LTR, viral RNA is expressed in various mouse tissues, including skin, kidney, spleen, and lymph nodes. A proportion of the heterozygous mice develop cataracts, cutaneous papillomas, and renal disease (24,26,27). We recently reported that Tg26 mice without cutaneous papillomas did not develop lymphomas, but that 15% of Tg26 mice with cutaneous papillomas spontaneously developed leukemia/lymphoma by 1 y of age, characterized by widespread lymphadenopathy, splenomegaly, and extranodal involvement of the liver, gastrointestinal tract, and central nervous system (25).…”
Section: Significancementioning
confidence: 99%
“…Transgene RNA, assessed by Northern analysis, is expressed abundantly in muscle and skin and to a lesser extent in kidney, lymphoid tissue, intestine and eye. Other phenotypes included focal glomerulosclerosis, 19 cutaneous papillomas 20 and, in the homozygote, wasting and early death. 21 Transgene status was determined by Southern blotting, as described previously.…”
Section: Transgenementioning
confidence: 99%
“…After paraffin embedding, 4 m sections were cut. Histochemical detection of HIV-1 envelope protein was performed exactly as previously described, 20 using a polyclonal sheep anti-gp120 antiserum (developed by M Phelan and obtained from ARRRP). This antiserum or its control, normal sheep serum, were diluted 1:2000 and applied to the sections for 1 h at 37°C.…”
Section: Immunohistochemistrymentioning
confidence: 99%